STATEGI PENGEMBANGAN OBJEK WISATA DANAU ATAS DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Muhammad Ihsan; Febriandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the potential and development strategies of the Danau Atas tourism object located within the Alahan Resort/Villa Resort area in Nagari Alahan Panjang, Solok Regency, by employing the SOAR (Strengths, Opportunities, Aspirations, Results) analytical approach. The Danau Atas area possesses major attractions in the form of a cool highland natural panorama, scenic lake landscapes, and opportunities for family-oriented recreation and nature-based relaxation. However, the management and development of this tourism area have not yet been optimal, particularly in terms of supporting facilities, enhancement of tourism attractions, and community involvement in tourism management.This research adopts a descriptive qualitative method, with data collected through field observations, documentation, and interviews with key stakeholders, including resort managers, local communities, and relevant parties involved in tourism development. The SOAR analysis is applied to identify the internal strengths of the tourism area, available development opportunities, the aspirations of managers and the local community, as well as the expected outcomes of community-based tourism development strategies in the Danau Atas area. The findings indicate that the primary strengths of the Danau Atas tourism object lie in its attractive natural scenery, the availability of amenities such as villas and resorts, and its strategic location along the Alahan Panjang tourism route. Development opportunities include the growing trend of highland nature tourism, digital promotion, and inter-stakeholder collaboration in tourism management. Development aspirations are directed toward improving facilities, strengthening human resource capacity, and developing tourism attractions based on local culture. The recommended strategies include enhancing the quality of amenities, adding supporting facilities such as gazebos and sanitation infrastructure, and strengthening community participation to realize a sustainable and competitive Danau Atas tourism destination.